A new species of the squat lobster genus Galathea Fabricius, 1793 from Lakshadweep, India (Crustacea: Decapoda: Galatheidae) - Sureandiran, B.; Divya, P.r.; Naeem, U.p. Mohammed; Sundaramanickam, A.; Kumar, T.t. Ajith (Zootaxa, 2026)
A new species of galatheid squat lobster, Galathea balasubramaniani sp. nov. is described from Lakshadweep Island, India. The G. balasubramaniani sp. nov. belongs to the ‘G. mauritiana’ group, identified through having a pterygostomian flap with 1 or 2 spines and an uninterrupted mesogastric ridge. This group includes: G. acis Macpherson & Robainas-Barcia, 2015, G. aequata Macpherson & Robainas-Barcia, 2015, G. ahyongi Macpherson & Robainas-Barcia, 2015, G. mauritiana Bouvier, 1914 and G. senta Macpherson & Robainas-Barcia, 2015. The G. balasubramaniani sp. nov. resembles G. mauritiana Bouvier, 1914, but differs based on the presence of an epipod on P1, and P2 with propodus 4.2–4.7 times as long as wide and the merus with the proximal spine reaching or slightly over-reaching the distal margin of the article. Maximum Likelihood analysis of the new species, using mitochondrial genes cytochrome c oxidase (COI) and 16S rRNA also supported the findings and suggests that G. balasubramaniani sp. nov. is closely related to G. mauritiana, with pairwise genetic distances estimated at 6.0–14.3 % (COI) and 3.1–16.9% (16S rRNA).